2012
DOI: 10.1159/000339616
|View full text |Cite
|
Sign up to set email alerts
|

High-Intensity Focused Ultrasound and Cryotherapy as Salvage Treatment in Local Radio-Recurrent Prostate Cancer

Abstract: Background: Salvage high-intensity focused ultrasound (HIFU) and cryotherapy (CRYO) have emerged as interesting alternatives in the treatment of local radio-recurrent prostate cancer. Currently, recommendations concerning the use of CRYO and HIFU in the salvage setting are still evolving. Aim: The objective of this review was to analyze the results from studies on CRYO and HIFU as salvage treatment in local radio-recurrent prostate cancer. Materials and Methods: A National Center for Biotechnology Information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…Salvage radical prostatectomy for recurrence after radiotherapy is an accepted alternative although it is a demanding surgical procedure involving serious morbidity and risk of surgical complications (14) . Optimal local treatment of recurrence is controversial, with alternative treatments depending on availability of instrumentation and risk, age and comorbidities of the patient (2,15). New treatment modalities with minimally invasive techniques such as percutaneous cryotherapy and thermal ablation, have gained popularity for treatment of men with prostate cancer (2).…”
Section: Original Papermentioning
confidence: 99%
“…Salvage radical prostatectomy for recurrence after radiotherapy is an accepted alternative although it is a demanding surgical procedure involving serious morbidity and risk of surgical complications (14) . Optimal local treatment of recurrence is controversial, with alternative treatments depending on availability of instrumentation and risk, age and comorbidities of the patient (2,15). New treatment modalities with minimally invasive techniques such as percutaneous cryotherapy and thermal ablation, have gained popularity for treatment of men with prostate cancer (2).…”
Section: Original Papermentioning
confidence: 99%
“…5,6 sHIFU and sCT have been shown to have a similar comorbidity profile. 7 Whilst there are reports on comparing oncological outcomes with ablation technique versus salvage prostatectomy, 8 there are no reports with local salvage treatment versus those without salvage therapy (NST). Herein, we performed a propensity-score matched analysis with a large multi-institutional radiation therapy database (where patients received standard of care but did not have salvage local prostate treatment) compared with a prospective singleinstitution database on salvage local ablative therapies, to examine for differences in cancer specific survival (CSS) and overall survival (OS).…”
Section: Introductionmentioning
confidence: 99%
“…Another larger study reported urethral stricture in 5.5%, a bladder-outlet obstruction requiring transurethral resection (TURP) in about 4% and the necessity of sling or artificial urinary sphincter (AUS) placement due to urinary incontinence in almost 3%. Related to the performed technique, perineal pain is a possible problematic complication of cryotherapy occurring in up to 8% ( 9 ).…”
mentioning
confidence: 99%
“…Currently, there are three commercially available devices (Sonablate – Focus Surgery Inc., Ablatherm – EDAP-TMS SA and Focal One – EDAP-TMS SA). It uses a transrectal piezoelectric ceramic transducer focusing on the target that causes thermal, mechanical and cavitation effects, producing a coagulative necrosis in the prostate ( 9 ). Temperatures achieved are above 80°C and there are safety features like a cooling system maintaining rectal mucosa at lower temperatures, a real time 7.5 Mhz.…”
mentioning
confidence: 99%